ANALISIS PENGARUH HARGA, KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN MEREK PELANGI KEMASAN 600ML DI SEMARANG - Murty, Dea; Khasanah, Imroatul (Diponegoro Journal of Management, 2015)
Consumer purchase decision is a decision regarding the preference for brands that exist in the set of choices. If consumers have a choice between making a purchase and do not make a purchase  or  option  to  use  the  time,  then  the  consumer  is  in  a  position  to  take  a  decision. Conversely, if the consumer does not have   alternatives to choose and actually forced to make certain purchases or take a particular action, then the only state with no other options this is not a decision. Many factors can influence purchasing decisions, including price, product quality and brand image. Purpose of this study was to analyze the affect of price, product quality and brand image on purchasing decisions. Object of this study is the bottled water packaging brand Pelangi600ml for sale from year 2011 to 2013 continued to decline. This research purpose is to analyze effect of price, product quality and brand image on purchase decision water brand in Semarang bottled water packaging brand Pelangi 600ml. The population in this study is that consumers who buy bottled water brand in Semarang bottled water packaging brand Pelangi 600ml. The sample in this study was 100 consumers. The sampling technique in this study conducted by purposive sampling technique. data type is primary. Methods of data collection using the questionnaire. The analysis technique used is multiple regression. The results of the analysis using SPSS showed that : Price positive and significant impact on purchasing decisions. Quality products positive and significant impact on purchasing decisions. Brand image positive and significant impact on purchasing decisions